The wrong side of the tracks: Starting school in a socially disadvantaged London borough. (June 2017) - Alsford, Elizabeth; Ralephata, Andrew; Bolderson, Sarah; Curtin, Martina; Parish, Esther; Klaber, Victoria; Griffin, Sue; Nash, Lisa; Cullen, Rachel; Musoke, Brenda; Bhalla, Sangheeta; Walker, Lindsay; et al.
Substantial evidence exists that social circumstances can affect children's language development. As a result many children in socially deprived areas start school with delayed language, which may persist and adversely affect their attainment. We assessed the language of children in seven reception classes in a London (UK) borough and followed the progress of children with English as their first language (E1L) and with English as an additional language (EAL) during their first 2 years at school. Significant differences were found between schools. The effect of social factors on performance was reflected in a high correlation between the mean language score for each school and the percentage of children in the school receiving the pupil premium. Many of the children with EAL had very low scores reflecting their limited exposure to English prior to starting school. Most of these children attended schools where children with E1L also had low scores increasing the demands on the schools and their teachers. Children who had low initial scores made modest but significant progress during their reception year but failed to improve further during year 1 despite having non-verbal ability appropriate for their age. These results support previous findings that social deprivation can seriously delay language development, and that many children start school with weak communication skills. They add to previous findings by showing that the level of delay may differ substantially across schools in the same borough, by reporting data on children with EAL and by showing that children struggle to improve their abilities in the first 2 years of school.